10th Latin American and Caribbean Conference for Engineering and Technology : megaprojects : building infrastructure by fostering engineering collaboration, efficient and effective integration and innovative planning (Latin American and Caribbean Consortium of Engineering Institutions, 2012)
Conferencia Internacional Latinoamericana sobre la Construcción de Infraestructura y el Fomento de la Colaboración en Ingeniería.